Quantifying soil movement by forest vehicles with corpuscular metal tracers - Haas, J.; Fenner, P. T. [UNESP]; Schack-Kirchner, H.; Lang, F. (My University, 2018)
Bulk soil movement caused by human impact is hard to quantify. In forestry the bulk soil displacement by passage with heavy machinery is virtually unknown. We present a new method to measure such soil movement with hollow corpuscular metal tracers (16 mm pieces of thin-walled metal pipes made of iron, aluminum, copper and lead) and a metal detector. The tracers are installed minimally invasive into the soil before and located with a metal detector after logging operations. To correctly interpret these measurements it is crucial to know about the accuracy and precision of the method, especially under varying soil moisture content or if different tracer materials are present. To address these questions a series of experiments under controlled conditions on soils with differing iron oxide concentrations were conducted. Best performance on all soils showed Al-tracers, whereas Fe-tracers are limited by increasing Fe-oxide concentrations. Cu and Pb failed. Material specific detection is limited to soils poor in Fe-oxides. Tracers were accurately detectable up to 15–20 cm depth depending on soil moisture. As the signals of the metal detector leave room for interpretation handling needs individual training to obtain unbiased results. In a case study from timber harvesting operations on sloping terrain in Central Europe the tracers where successively moved by each passage of the harvesting machines. After a complete operating cycle the histogram of displacement matched a heavy tailed distribution with a median of around 10 cm and a maximum of several meters. Displacement was reduced by the use of a traction supporting winch. However uncertainty remains whether tracer displacement exactly reflects bulk soil movement.
Keywords: Erosion; Logging; Soil movement